Memoirs sherlock holmes - Doyle, Arthur Conan (Naples Florida: Trident press international, 2001)
It is of the highest importance in the art of detection to be able to recognise out of a number of facts which are incidental and which are vital
Silver blaze -- The yellow face -- The stock- broker's clerk -- The "gloria scott" -- The musgrave ritual -- The president patient -- The greek interpreter -- The naval treaty -- The final problem
English